Overview of Image Smoothing Algorithms. Issue 1 (April 2021) - Li, Pei; Wang, Hongjuan; Yu, Mengbei; Li, Yeli
Abstract: In the process of image generation and transmission, it is easy to be polluted and affected by various kinds of noise, which reduces the quality of the image. In order to avoid the adverse effects of image processing and image visual effect, we can use image smoothing technology to improve the adverse effects, so as to make the image clearer. There are a variety of image smoothing techniques, which had great smoothing effect, but there are also different defects. Based on the analysis of different noise models, this paper uses mean smoothing, median smoothing, Gaussian smoothing, bilateral filtering and other techniques to study and analyse the image processing algorithm, the implementation method and efficiency, which provides efficient theoretical value for image processing and image visual effect in various fields involved in image processing.